(3QSGdI aj GdMceIs
(3ChdgG (B:s
(3aUd GdMceI fJjLI GdMceI hGdYde fJjLI GdeYQaI aef dGMceI dg dG Mce dg hef dGeYQaI dg dGYde dg HGddg aGdMGce GdYGde s
(3BNQgG (B:s
(3hGYJRd Yf cd ef ZjQ GdMHjH GdhGdj hEPG SgQJ hUMJ fdJ ebGege Je GdcJGH HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCRgQjI (B(3/33580) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs